Clinical-pathological study of AIDS descriptive criteria and evaluate the role of HIV awareness among infected patients visiting public health centers in Thi Qar Governorate between November 2023 and February 2024 - alyasiri, Haider Mohammed; Abdulhussien, Adeeb Abdulally; Mousa, Hameed Naeem; Abass, Fadhil; Ali Hasan, Zainab Mohammed; Fatihallah, Mohammed Hassan; Jawad, Zainalaabdeen Basim; Chasib, Hayder Hasan; Kafel, Mustafa Kadhim; Al-Rahman, Ahmed Dhiaa (Journal of Neonatal Surgery, 2025)
Acquired immunodeficiency syndrome (AIDS) represents the advanced stage of HIV infection. HIV targets and infects the body's white blood cells, and its incidence has been on the rise in Thi-Qar city, Iraq. This study aims to assess the incidence of HIV infection in this region from 1986 to 2024.This retrospective cross-sectional study was conducted from November 30, 2023, to February 24, 2024. A total of 144 patients diagnosed with AIDS in Thi-Qar province, Iraq, were included. Data were obtained from the Thi-Qar Medical Institute and the Health Directorate's database, following legal and ethical approval. The data collection process involved a thorough review of each patient's medical history and physical examination. HIV diagnosis was confirmed using PCR techniques, and statistical analysis was performed using SPSS software.The Results were among the 144 patients, 117 were male (81%) and 27 were female (19%). The study identified various transmission routes: 7% of patients had a history of blood transfusion, 26% were infected through heterosexual contact, 5% through homosexual contact, 2% through both heterosexual and homosexual contacts, 1% through vertical transmission, 13% through husband-to-wife transmission, and 46% through unknown causes. The incidence of HIV infection gradually increased, from a single case in 1986 to 21 cases in 2019. The number of cases then rose more sharply, reaching a peak of 144 patients by early 2024. The study highlights the increasing incidence of HIV infection in Thi-Qar province, particularly from 2019 to 2024. The most common transmission routes were unknown causes, heterosexual contact, husband-to-wife transmission, blood transfusion, homosexual contact, and vertical transmission. The highest incidence was observed among young adults aged 20-50 years